A thermal-hydraulic analysis model of printed circuit heat exchangers for system simulation using Modelica. Issue 12 (2nd December 2021) - Ding, Hao; Li, Wenhuai; Duan, Chengjie; Xu, Hong; Ding, Peng; Zhang, Yaoli; Hong, Gang
ABSTRACT: Supercritical CO2 (S-CO2 ) Brayton cycle is one of the alternative energy conversion technologies for generation IV nuclear energy systems. Printed circuit heat exchanger (PCHE) is one of the key components in S-CO2 Brayton cycle. Although PCHE has dedicated steady-state models, transient models that can be applied to precise analysis of systems remain to be developed. The deviations brought by different flow and heat transfer correlations needs to be studied in simulations of PCHE, considering that the disparity of results obtained by various correlations under different working conditions are more obvious in iterative calculations. We developed a PCHE model in Modelica according to the existing S-CO2 flow and heat transfer correlations. To benchmark the model, steady-state results are compared with the results obtained by Fluent. The deviations caused by various flow and heat transfer correlations are analyzed. Transient analysis is performed to compare different control strategies when reducing the power of PCHE. According to the results of the transient simulation, PCHE used as a pre-cooler in S-CO2 Brayton cycle can quickly respond to transient variations. Both steady-state and transient results verified the reliability of the PCHE model, which suggests that the model can be utilized for the system analysis of S-CO2 Brayton cycle.